The Normative Basis of the Legal Status of a Military Serviceman on the Lands of Ukraine in the 19th Century - Holovko, B. H. (Вісник Харківського національного університету внутрішніх справ, 2025)
In search of an answer to the question of the reasons for the unprovoked aggression of the Russian Federation against Ukraine, researchers turn to the first steps in the common history of the two states, including in the field of military law. One of the key problems in this direction is the clarification of the legal status of a serviceman on the territory of Ukraine during the period of Modern History. The issue is complicated by the fact that as a result of the partitions of Poland in the late 18th century and early 19th century, Ukrainian lands were annexed to foreign states, which initiated the absorption of Ukrainian law by the legal systems of the metropolitan states. It has been proven that the state's attitude towards the military, the system of mutual rights and obligations was determined depending on the territory of which state the Ukrainian military was located. It can be assumed that the legal status of a military serviceman was more democratic if we are talking about his definition by the law of the Austrian or, over time, the Austro-Hungarian Empire. At the same time, the rights of the military under the law of the 19th century Russian state were subject to excessive administration. It is determined that the accession of the legal system of the Ukrainian territories had certain positive consequences as a manifestation of legal acculturation. At the same time, it is quite obvious that the spread of foreign legal systems on the lands of Ukraine had the negative consequence of forgetting the very original and attractive local features of law that had developed in previous times and provided for much more significant protection of the rights of the military, his participation in democratization of the armed forces through participation in leadership elections, accountability, a system of incentives, a fair system of punishments, etc. It has been established that the law, primarily of the Russian Empire, in attempts to determine the legal status of the military, first of all, turned to the class and social origin of the person, accordingly increasing the scope of rights of officers, senior and higher and limiting the rights of ordinary servicemen. Moreover, the military laws of the Russian Empire contained certain oppressions regarding the recruitment and career growth of residents of Ukrainian lands. It has been proven that, at least until the military reform of 1874, the possibility of protecting the rights by the military in court, was severely limited due to the imperfect organization of military courts. In our opinion, considering the above circumstances may be useful in the process of improving the military law of Ukraine.